A Comparative analysis of DPFC with UPQC performance using various control techniques to Improve Power Quality in Smart Grid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electricity generation from the Wind and sun based photovoltaic (PV) frameworks are profoundly relies on climate conditions. Their irregular nature prompts vacillations in their yield. In this manner, the requirement for quick pay of vitality transmission and circulation frameworks is progressively significant.  This paper explores examination of intensity quality issues of utility associated with Smart Grid utilizing Unified Power Quality Conditioner (UPQC) and Distributed Power Flow Controller (DPFC) device. Improvement of PQ in SG from  disrupting impacts happened power structure controller utilized DPFC. From start, proposed structure power stream is surveyed and Multi Wavelet Transform (MWT) is used to incorporate extraction system of power parameters for PQ agitating impacts. In event that the yield signal has any aggravations, at that point yield signal is constrained by proposed controller based DPFC. Proposed calculation is utilized to hold supported DC-link voltage of DPFC by controlling yield voltage to enhance PQ. Modeling of solar PV-Wind Hybrid Micro-grid system increases power quality of system. In this paper, a new method was proposed with  an Elephant Herding Optimization(EHO) based on DPFC control scheme, which is compared such as ANFIS with FA based UPQC, ANFIS with FA based DPFC , CFA with PSO based UPQC,CFA with PSO based DPFC and modified EHO with RNN technique based UPQC . The main objective of proposed method is to detect and control PQ problems in SG. In order to achieve the objective, simulation is carried out in MATLAB SIMULINK model.